Artysta między godnością a zawstydzeniem. "Impresje" nie tylko o dokonaniach artystycznych - Nadrowski, Henryk (Studia Theologica Varsaviensia, 2017)
The achievements of each artist are connected to his craftsmanship, professionalism, and most importantly his vocation. His personal decisions regarding his art have a direct impact on it, as he can act in a positive and responsible way, or negative with destructive and demoralizing way. Often we hear of the “priesthood” of an artist and of his prophetic mission, which becomes an annunciation and a kind of epiphany of beauty. To that end, many say that artists through their work bring salvation to many. In many ways, art plays an essential part in fulfilling Theology by giving it a commentary. In a specific way it is connected to sacramental art, which has many layers. This sort of art should always be decent and respectful and at the same time make it easier for people to connect to God, during the liturgy, as well as during the personal prayer, meditation, contemplation and adoration. These pieces of art should always create a sense of unity and harmony. After all, we always look and search for a deeper meaning of art, not forgetting its iconological and theological sense. When we talk about art that is considered shameless, we also touch the artist’s lack of professionalism, inability to create high class art; its cheapness and plagiarism, but also it’s destructive, full of degradation and demoralizing context. In the context of the religious sacrum, those negative behaviors in art, together with its loss of prophetic and sacred meaning, often lead to: profanation, heresy, blasphemy, and idolatry. A great abuse of freedom of expression that cannot be tolerated is an absolute ignorance when it comes to God, dismissing God altogether while promoting self. At the same time, the recipient is ignored and disdained. Still just as valid today are the importance of dialogue and the cooperation of three different backgrounds: The artists, investors and consumers. The achievements of the artists should not only enhance the heritage of given generation, but most importantly lift up the spirit of believers and even making easier for them to reach salvation